Ancestral houses in Silay City Negros Occidental - Cabalinan, Jean S. (1997.)
"Remnants of a genteel era, ancestral houses stand like guardians of recent past, a past defined by luxury, opulence and a deed-seated pride in one's origin and ancestry." (Mariza Azcona Bonin). Silay Ancestral house were generally built of stone and wood in turn of the century (late 1800's - early 1900's). It was the heyday of Silay when the city's economy was experiencing a rapid growth and the province of Negros was slowly integrating into the American government. These houses were built according to the taste and specifications of the owners. The ancestral houses in Silay city reveal the people's personalities and lifestyles. As hacienderos, their houses were big originally built in the middle of a large farm. Everything inside the house were imported. Designs were adopted from European styles. It was the time when the city was called the "Paris of Negros". Silay was described as little Paris because of its buildings and houses. These houses were open to all. Everyone if welcome to enter and join the family. They speak of an era when expanded families all livd under one roof and were served by dozens of household help, when art and music were part of day-to-day living, and when lifestyles were carved out of sugar, and life was sweet.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Architecture, Domestic -- Philippines -- Negros Occidental -- Silay City